Corneal epithelial debridement for diagnosis and therapy of ocular surface disease. (20th October 2014) - McGrath, Lindsay A; Lee, Graham A
<x xml:space="preserve">Abstract</x> Background There is a wide range of ocular surface conditions that can be diagnosed or treated with epithelial debridement. The purpose of this study is to analyse the indications, instrumentation and outcomes of corneal epithelial debridement for anterior segment pathology. Methods One hundred and thirty‐three eyes of 129 patients with ocular surface disease were treated with epithelial debridement. Different methods were used, appropriate to the specific disease, aetiology and outcome measure. Results The mean patient age was 56 years and 81 (60.9 per cent) were male. Sixty‐two eyes (46.6 per cent) were undertaken for diagnosis and 71 (53.4 per cent) for therapy. Common indications for diagnostic corneal debridement included infective keratitis 48 (36.1 per cent), neoplasia 14 (10.5 per cent), while those for therapeutic corneal debridement included recurrent erosion 30 (22.5 per cent) and band keratopathy 16 (12.0 per cent). The most common post‐operative complication was pain, occurring in all patients to some extent. Band keratopathy was seen to recur in two (12.5 per cent) of the treated eyes and there was a single relapse of recurrent erosion during the follow‐up period. Conclusion The techniques presented can be undertaken in the office rather than a day procedural unit, improving time and cost‐effectiveness for the ophthalmologist and patient.